2017 19th International Conference on Intelligent System Application to Power Systems (ISAP) 2017
DOI: 10.1109/isap.2017.8071420
|View full text |Cite
|
Sign up to set email alerts
|

Is big data sufficient for a reliable detection of non-technical losses?

Abstract: Non-technical losses (NTL) occur during the distribution of electricity in power grids and include, but are not limited to, electricity theft and faulty meters. In emerging countries, they may range up to 40% of the total electricity distributed. In order to detect NTLs, machine learning methods are used that learn irregular consumption patterns from customer data and inspection results. The Big Data paradigm followed in modern machine learning reflects the desire of deriving better conclusions from simply ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…There may be also covariate shifts for other master data, such as for the customer class or for the contract status. 2 We now aim to correct n different biases at a same time, e.g. for class imbalance as well as different types of covariate shift.…”
Section: Reduction Of Biasesmentioning
confidence: 99%
See 3 more Smart Citations
“…There may be also covariate shifts for other master data, such as for the customer class or for the contract status. 2 We now aim to correct n different biases at a same time, e.g. for class imbalance as well as different types of covariate shift.…”
Section: Reduction Of Biasesmentioning
confidence: 99%
“…We have previously shown that in many cases, the set of inspected customers is biased. 2 A reason for that is that past inspections have been largely focused on certain criteria and were not sufficiently spread across the population. This paper builds on top of our previous contributions and aims at bias reduction in data, and further at more generalizable NTL predictors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…the set of customers to generate inspections for) having different distributions. We have shown in [8] that the sample of inspected customers may be biased, i.e. it does not represent the population of all customers.…”
Section: Related Workmentioning
confidence: 99%